2019
DOI: 10.3389/fmicb.2019.02128
|View full text |Cite
|
Sign up to set email alerts
|

Life After Secretion—Yersinia enterocolitica Rapidly Toggles Effector Secretion and Can Resume Cell Division in Response to Changing External Conditions

Abstract: Many pathogenic bacteria use the type III secretion system (T3SS) injectisome to manipulate host cells by injecting virulence-promoting effector proteins into the host cytosol. The T3SS is activated upon host cell contact, and its activation is accompanied by an arrest of cell division; hence, many species maintain a T3SS-inactive sibling population to propagate efficiently within the host. The enteric pathogen Yersinia enterocolitica utilizes the T3SS to prevent phagocytosis and inhibit inflammatory responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 71 publications
1
29
1
Order By: Relevance
“…Maleimide based needle staining. To visualize the injectisome needles, expression of SctF S5C 46 was induced from plasmid. Protein expression was induced with 0.4-1.0% L-arabinose at the temperature shift.…”
Section: Methodsmentioning
confidence: 99%
“…Maleimide based needle staining. To visualize the injectisome needles, expression of SctF S5C 46 was induced from plasmid. Protein expression was induced with 0.4-1.0% L-arabinose at the temperature shift.…”
Section: Methodsmentioning
confidence: 99%
“…92 But how does Y. enterocolitica prevent secretion at low pH? To determine if the absence of secretion 93 is due to a complete disassembly of injectisomes at that pH, we visualized the needles at different pH 94 values and over time by labeling an introduced cysteine residue with a maleimide-linked dye (Milne-95 Davies et al, 2019). The needles were stable at pH 4 over continued time periods ( Fig.…”
mentioning
confidence: 99%
“…While in Shigella and Yersinia , almost all bacteria assemble injectisomes at 37°C (Burgess et al, 2020; Milne‐Davies et al, 2019; Wiley et al, 2007), bimodal expression of injectisome components is observed in Salmonella and Pseudomonas , where a large subpopulation does not assemble any injectisomes (Rietsch and Mekalanos, 2006; Rundell et al, 2016; Sturm et al, 2011). Salmonella uses division of labor and bet‐hedging strategies for more efficient infection and increased survival if conditions change (Davis and Isberg, 2019; Weigel and Dersch, 2018).…”
Section: Distribution Of T3ss Within Bacteria and The Populationmentioning
confidence: 99%
“…In Y. enterocolitica , the T3SS is homogenously expressed and bacteria are able to survive and restart division following secretion. These observations imply that Y. enterocolitica aim to maximize individual survival chances (Milne‐Davies et al, 2019). In the case of S. flexneri and S. sonnei , the Shigella virulence plasmid (pINV), which contains the injectisome, even harbors multiple toxin–antitoxin (TA) systems that aid in maintaining the plasmid during cell division (McVicker and Tang, 2017; Sayeed et al, 2000) and suppress the rise of faster‐growing “cheaters”—an indication that like Yersinia , Shigella focuses on the survival of individual bacteria during infection, which is also indicated by the very low infectious dose (DuPont et al, 1989).…”
Section: Distribution Of T3ss Within Bacteria and The Populationmentioning
confidence: 99%
See 1 more Smart Citation